Successful treatment of a Candida auris intra-articular infection - Roberts, Scott C. (Emerg Microbes Infect, 2019)
A 78-year-old woman with a long-term ankle spacer with antibacterials developed an intra-articular Candida auris infection. Treatment with systemic antifungal therapy plus an amphotericin B moulded cement spacer was successful.